Inuit uses of weather, water, ice, and climate indicators to assess travel safety in Arctic Canada, Alaska, and Greenland: a scoping review - Breanna Bishop; Emmelie Paquette; Natalie Carter; Gita Ljubicic; Eric C.J. Oliver; Claudio Aporta (FACETS)
Environmental indicators are naturally occurring variables, conditions, and events that are used to assess and monitor environmental conditions and change. Inuit throughout Inuit Nunaat (Inuit circumpolar homelands) observe and experience environmental indicators as they travel year-round for harvesting and other cultural practices. Inuit draw on their observations of current conditions and their knowledge of weather, water, ice, and climate (WWIC) indicators, when seeking to predict and understand conditions that impact safe travel. This scoping review documents the types and diversity of WWIC indicators articulated in peer-reviewed and grey literature as being used by Inuit in Canada, Alaska, and Greenland to assess travel safety. Two reviewers independently screened 512 studies using pre-determined eligibility criteria and 123 studies were included for review. A total of 163 unique WWIC indicators were used across 85 communities in Canada, Alaska, and Greenland. Indicators reflect a broad range of ways that Inuit experience their environment, through sight, feel, and sound. Indicators can be considered as causal, conditional, or predictive (or a combination thereof), where knowledge of the interactions among various indicators is especially important to support safe travel. Identified gaps and future research directions included assessing key indicators to better target development of locally relevant research and information services.